A practical guidance on the prevention and treatment of childhood respiratory syncytial virus infection in Kurdistan - Haleem, Azad A.; Alsaqee, Azhar; Dizayi, Lana A.; Hanna, Sasan L.; Rabaty, Abbas A.; Pedawi, Serdar; Salih, Aso F. (Frontiers in Pediatrics, 2025)
Without an available vaccine in Kurdistan, Respiratory Syncytial Virus (RSV) infection threatens younger children, burdens the healthcare system and contributes to household expenditure on health. Immunoprophylaxis remains the only preventive option in Kurdistan. Expert pediatricians recommend palivizumab to children at RSV risk; particularly infants (1) born within 29 gestational weeks and <1-year-old at RSV season start, (2) born premature (>29 gestational weeks) at risk for RSV hospitalization, (3) with congenital lung disease requiring oxygen therapy for >1 month and are <2 years old at RSV season start, and (4) with hemodynamically significant congenital heart disease and acyanotic heart and who are <2 years of age at RSV season start. We call onto health authorities to support palivizumab immunoprophylaxis to all children at risk for RSV.